Benign lymphangioendothelioma: a clinical, histopathologic and immunohistochemical analysis of four cases. (16th September 2013) - Wang, Lei; Chen, Liuqing; Yang, Xichuan; Gao, Tianwen; Wang, Gang
<x xml:space="preserve">Abstract</x> Background Benign lymphangioendothelioma represents a rare lymphatic vascular proliferation characterized by proliferation of irregular and thin‐walled vessels dissecting amongst dermal collagen. Immunohistochemical analysis has been lacking in most previously reported cases. Methods Herein, we report the clinical and histopathologic characteristics of four cases of benign lymphangioendothelioma. Immunohistochemical study was completed for all lesions. Results All lesions presented as large, red to brown patches or plaques. Three lesions were located on the thigh and one lesion was located on the neck. Histopathologically, all lesions showed proliferation of anastomotic or retiform thin‐walled vessels with a single layer of endothelial cells that dissect the dermis. D2‐40 and Prox1 immunostains were positive and Wilms tumor 1 (WT‐1) immunostain was negative in all cases. Conclusion Benign lymphangioendothelioma represents a lymphatic vascular proliferation. A lack of expression of WT‐1 suggests it represents a lymphatic vascular malformation.